Software architecture for YOLO, a creativity-stimulating robot - Alves-Oliveira, P. (2020)
YOLO is a social robot designed and developed to stimulate creativity in children through storytelling activities. Children use it as a character in their stories. This article details the artificial intelligence software developed for YOLO. The implemented software schedules through several Creativity Behaviors to find the ones that stimulate creativity more effectively. YOLO can choose between convergent and divergent thinking techniques, two important processes of creative thought. These techniques were developed based on the psychological theories of creativity development and on research from creativity experts who work with children. Besides promoting creativity, this software allows the creation of Social Behaviors that enable the robot to behave as a believable character. We built 3 main social behavior parameters: Exuberant, Aloof, and Harmonious. These behaviors are meant to ease immersive play and the process of character creation. The 3 social behaviors were based on psychological theories of personality and developed using children's input during co-design studies. Overall, this work presents the design, development, and usage of social robots that might nurture intrinsic human abilities, such as the ability to be creative.